1993
DOI: 10.1002/bdd.2510140507
|View full text |Cite
|
Sign up to set email alerts
|

Relative bioavailability of two disopyramide capsules in humans based on total, unbound, and unbound enantiomer concentrations

Abstract: The relative bioavailability of two 100-mg disopyramide formulations which showed almost an 8- to 10-fold difference in their dissolution rates at pH 1.2 and 6.8 was determined in eight healthy subjects using a randomized block design. Although no significant differences in relative bioavailability were observed between the two formulations when based on the total disopyramide concentration, an almost 30 per cent difference in the extent of bioavailability was observed when assessed in terms of the unbound (+/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Numerous studies have demonstrated differences in the dissolution and absorption of crystalline forms of the racemate vs. the individual enantiomers (e.g., ketoprofen [12], disopyramide [13], lansoprazole [14], verapamil [15], tramadol [16], anesthetic drugs [17], and ibuprofen [18]). Drug absorption from the gastrointestinal (GI) tract is largely passive and mediated by drug solubility and permeability; blood levels [e.g., the area under the curve (AUC)] are also generally a reflection of the dose administered or concentration released over time.…”
Section: Supercritical Fluid Chromatography (Sfc)mentioning
confidence: 99%
“…Numerous studies have demonstrated differences in the dissolution and absorption of crystalline forms of the racemate vs. the individual enantiomers (e.g., ketoprofen [12], disopyramide [13], lansoprazole [14], verapamil [15], tramadol [16], anesthetic drugs [17], and ibuprofen [18]). Drug absorption from the gastrointestinal (GI) tract is largely passive and mediated by drug solubility and permeability; blood levels [e.g., the area under the curve (AUC)] are also generally a reflection of the dose administered or concentration released over time.…”
Section: Supercritical Fluid Chromatography (Sfc)mentioning
confidence: 99%
“…Disopyramide is a type Ia anti-arrhythmic agent used clinically for the treatment and prophylaxis of supraventricular and ventricular arrhythmias. Disopyramide has a relatively narrow therapeutic plasma concentration range (2-5 µg mL − 1 ) and shows concentration-dependent binding to plasma proteins in man (Hasselstrom et al 1991 ;Takahashi et al 1991bTakahashi et al , 1993a.…”
Section: Introductionmentioning
confidence: 99%
“…Although disopyramide is available commercially as a racemic mixture, the pharmacokinetic properties of each enantiomer have been reported to be different in man and animals (Cook et al 1982 ;Lima et al 1985 ;Giacomini et al 1986 ;Takahashi et al 1993a ;Masuhara et al 1995). Plasma protein binding of (S )disopyramide is higher than that of (R)-disopyramide in man, and the total clearance of unbound (S )-disopyramide is also higher than that of (R)-disopyramide (Lima et al 1985 ;Takahashi et al 1991a).…”
Section: Introductionmentioning
confidence: 99%